To Say or Not to Say: Medical and Social Project - Liana N. Abramova (Eco-Vector, 2020)
Mental health and psychological education activities are being carried out in Moscow (the Russian Federation), along with measures aimed at prevention of social stigma in mental health care. The medical, social and educational project To Say or Not to Say has been developed by a group of experts from the Mental-health clinic No. 1 named after N.A. Alexeev, for Moscow residents. The title chosen for the project urges participants to make a choice: continue living with their problems or take a step towards solving them. A new educational activity format has been created and tested in the course of the project, and this format provides an opportunity to largely overcome the stigmatizing barriers that prevent people from seeking psychological and psychiatric help in Moscow. Sixteen events involving over 7,000 citizens have been held, and the psychiatrists engaged in the project have spent 2,280 man-hours in this volunteering activity. We believe that this educational activity could help to overcome social stigma in psychiatry, further research is needed to measure the effect of our educational project on social stigma associated with mental health.